POTENSI WISATA BAHARI DALAM MENDUKUNG PARIWISATA DI PULAU SANGIANG, BANTEN - Aisyah Zhafirah; Rizki Nurul Nugraha (Jurnal Inovasi Penelitian, 2022)
Indonesia occupies the second position in Asia and seventh in the world in the category of the largest country which has 1/3 of the land area and the ocean with 2/3 of the total area. There are thousands of islands in Indonesia with exotic sea charms that make it possible to have diverse natural tourism potential, and one type of tourism that Indonesia has is Marine Tourism. Therefore, this study aims to identify the potential for marine tourism owned by Sangiang Island, Banten. This research is a qualitative descriptive research, using survey and interview techniques. The analytical method used is SWOT (Strengths, Weaknesses, Opportunities, Threats). The results of this study indicate that marine tourism on Sangiang Island, Banten has the potential to become a tourist destination that can attract many visitors. However, this potential still has many obstacles that need to be managed and rearranged professionally in order to attract more tourists to visit. The local community of Sangiang Island, Banten still really needs both capital and moral support from the government to support the development of tourism there.